Cambodia : Technical Assistance Report-Government Finance Statistics. (IMF Staff Country Reports; Country Report ;, 2020)
As part of Cambodia's participation in the Japan-funded Government Finance Statistics (GFS) and Public Sector Debt Statistics (PSDS) project for selected Asian countries (JSA3),1 this mission conducted an in-country workshop (December 2-4, 2019) and provided follow-up technical assistance (TA) on GFS and PSDS (December 5-13, 2019).2 Both activities were aimed at strengthening compilation and dissemination of fiscal data in line the GFS Manual 2014 (GFSM 2014) and the PSDS: Guide (PSDSG) to support surveillance and decision making. At the request of the authorities, the TA mission participated in the inter-agency workshop on data consistency in macroeconomic statistics conducted by the Ministry of Economy and Finance (MEF) during December 5-6, 2019.